2020
DOI: 10.1101/2020.03.06.980607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered Sensorimotor-to-Transmodal Hierarchical Organization in Schizophrenia

Abstract: For decades, schizophrenia has been primarily conceptualized as a disorder of high-order cognitive functions with deficits in executive brain regions. Yet due to the increasing reports of early sensory processing deficit, recent models focus more on the developmental effects of impaired sensory process on high-order functions. The present study examined whether this pathological interaction relates to an overarching system-level imbalance, specifically a disruption in macroscale hierarchy affecting integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
1
1
2
Order By: Relevance
“…expansion might further result in disturbed cortical differentiation of unimodal and transmodal regions in EOS. A compression of the unimodal-to-transmodal cortical hierarchy was recently found in chronic adult-onset schizophrenia(51), contrasting with our observation of cortical-thalamic hierarchy expansion. Given age-dependent shifts in the macroscale cortical hierarchy(52), this inconsistence might due to their disparate stage of the illness and age of onset, or their usage of antipsychotic drugs.Further longitudinal works are needed to chart functional organization abnormalities of the thalamus and the cerebral cortex during the course of schizophrenia.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…expansion might further result in disturbed cortical differentiation of unimodal and transmodal regions in EOS. A compression of the unimodal-to-transmodal cortical hierarchy was recently found in chronic adult-onset schizophrenia(51), contrasting with our observation of cortical-thalamic hierarchy expansion. Given age-dependent shifts in the macroscale cortical hierarchy(52), this inconsistence might due to their disparate stage of the illness and age of onset, or their usage of antipsychotic drugs.Further longitudinal works are needed to chart functional organization abnormalities of the thalamus and the cerebral cortex during the course of schizophrenia.…”
contrasting
confidence: 99%
“…A cortical hierarchy dissociating sensory from transmodal regions has been implicated in cognitive processing, describing a functional processing axis from perceptual/action towards abstract cognition functions including social cognition and memory (Margulies et al, 2016; Mesulam, 1998). At the same time, a compression of the unimodal-to-transmodal cortical hierarchy was recently found in chronic adult-onset schizophrenia (Debo Dong et al, 2020), in contrast with our findings of expansion. Given age-dependent shifts in the macroscale cortical hierarchy (Dong, Margulies, Zuo, & Holmes, 2021), this inconsistence might due to their disparate stage of the illness and age of onset, or their usage of antipsychotic drugs.…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, a number of previous rs-fMRI studies have also discovered abnormal functional connectivity involving most of these regions (Mitchell et al 2001;Karbasforoushan and Woodward 2012). However, our identified abnormal brain regions were not fully consistent with a recent gradient study on SZ (Dong et al 2020 Mar 8). This inconsistent might be ascribed to differences in sample size (Button To investigate associations between abnormal gradients and clinical symptoms in SZ, we performed regression analyses using generalized additive models (GAMs) (Hastie and Tibshirani 1986;Hastie and Tibshirani 1995 (Torrey 2007).…”
Section: Discussioncontrasting
confidence: 55%
“…This raises the possibility that multiple pathological processes, originating from opposing ends of the putative sensory-fugal hierarchy, may be involved in the disease. Interestingly, two recent functional imaging studies found evidence of atypical functional connectivity and integration between unimodal and transmodal cortices 96,97 . Our results show that these deficits in functional coordination may ultimately originate from underlying anatomical abnormalities, reflecting large-scale molecular and cellular gradients.…”
Section: Discussionmentioning
confidence: 99%